2014
DOI: 10.3389/fpsyg.2014.00665
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics and biases: interactions among numeracy, ability, and reflectiveness predict normative responding

Abstract: In Stanovich's (2009a, 2011) dual-process theory, analytic processing occurs in the algorithmic and reflective minds. Thinking dispositions, indexes of reflective mind functioning, are believed to regulate operations at the algorithmic level, indexed by general cognitive ability. General limitations at the algorithmic level impose constraints on, and affect the adequacy of, specific strategies and abilities (e.g., numeracy). In a study of 216 undergraduates, the hypothesis that thinking dispositions and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 73 publications
12
39
0
Order By: Relevance
“…There has been much debate about the individual differences involved in predicting normative responses to heuristics and biases tasks. Investigations have included general ability or intelligence, thinking dispositions (e.g., measures such as the cognitive reflection test) and numeracy (Klaczynski, 2014;Sinayev & Peters, 2015;Stanovich & West, 2008;Toplak, West, & Stanovich, 2013). Some show that normative responses are relatively unrelated to cognitive abilities (Stanovich & West, 2008), others claim that a high general ability is needed, but not sufficient without a favorable thinking disposition and high numeracy (Klaczynski, 2014).…”
Section: Numeracy and Cognitive Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…There has been much debate about the individual differences involved in predicting normative responses to heuristics and biases tasks. Investigations have included general ability or intelligence, thinking dispositions (e.g., measures such as the cognitive reflection test) and numeracy (Klaczynski, 2014;Sinayev & Peters, 2015;Stanovich & West, 2008;Toplak, West, & Stanovich, 2013). Some show that normative responses are relatively unrelated to cognitive abilities (Stanovich & West, 2008), others claim that a high general ability is needed, but not sufficient without a favorable thinking disposition and high numeracy (Klaczynski, 2014).…”
Section: Numeracy and Cognitive Abilitymentioning
confidence: 99%
“…Investigations have included general ability or intelligence, thinking dispositions (e.g., measures such as the cognitive reflection test) and numeracy (Klaczynski, 2014;Sinayev & Peters, 2015;Stanovich & West, 2008;Toplak, West, & Stanovich, 2013). Some show that normative responses are relatively unrelated to cognitive abilities (Stanovich & West, 2008), others claim that a high general ability is needed, but not sufficient without a favorable thinking disposition and high numeracy (Klaczynski, 2014). Some studies claim that thinking dispositions have a high predictive validity (Frederick, 2005;Toplak et al, 2013), whereas other studies indicate that such measures explain less variance than "pure" numeric ability (Sinayev & Peters, 2015).…”
Section: Numeracy and Cognitive Abilitymentioning
confidence: 99%
“…We also assessed participants' need for cognition. As described earlier, findings from previous studies (Klaczynski, ; Kokis et al, ; Morsanyi et al, ) have shown that need for cognition is related to probabilistic reasoning skills. Therefore, we expected that need for cognition would be related to participants' ability to compute posterior probabilities after our training sessions.…”
Section: Theoretical Backgroundmentioning
confidence: 54%
“…One of the aims of the present study was to examine the relative contributions of cognitive ability, thinking dispositions, cognitive reflection, numeracy, and scientific reasoning to overall bias susceptibility. Previous research has already brought evidence for the roles of all of these factors in susceptibility to reasoning and decision-making biases Klaczynski, 2014;Šrol & De Neys, 2019;Toplak et al, 2011). However, none of the studies yet to my knowledge managed to include in their analyses all of these predictors at once, thus possibly precluding the information about their relative contributions to susceptibility to cognitive biases.…”
Section: Predicting Individual Differences In Bias Susceptibilitymentioning
confidence: 99%
“…It should be mentioned, however, that since the roles of these factors are usually studied in isolation, their relative contributions to the adoption and maintenance of epistemically suspect beliefs are relatively unknown. In cognitive bias research, on the other hand, the roles of all of the abovementioned individual difference factors in susceptibility to various reasoning and decision-making biases is much better established (Klaczynski, 2014;Šrol & De Neys, 2019;Stanovich et al, 2016;Teovanović, Knežević, & Stankov, 2015;Toplak, West, & Stanovich, 2011). For these reasons, the six factorsi.e.…”
Section: Introductionmentioning
confidence: 99%